1985
DOI: 10.1136/bjo.69.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Studies on retinitis pigmentosa in man. II. Erythrocyte osmotic fragility.

Abstract: SUMMARY The osmotic fragility of erythrocytes from patients with genetically classified forms of retinitis pigmentosa (RP) has been studied. The mean fragility was increased in autosomal dominantly inherited RP, where the dystrophy was expressed regionally in the retina, with both rods and cones affected. In contrast it was normal in patients with the dominantly inherited disease, which leads to a diffusely distributed dystrophy of, predominantly, rod photoreceptor cells. Raised osmotic fragility of erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…R patients show an elevated osmotic fragility of their erythrocytes, whereas the fragility of the red blood cells of D patients is normal. 12 Future advances in research on AD RP will come from the application of new tests such as fundus reflectometry to patients already investigated by the techniques described in this study, longitudinal studies, the investigation of young family members, and histopathological and biochemical studies from donor eyes of properly characterised patients. From such studies it should become clearer whether our attempt at classifying AD RP has a valid basis, whether it needs to be refined and extended, and what are the underlying pathogenetic mechanisms.…”
Section: Disease Mechanismsmentioning
confidence: 99%
“…R patients show an elevated osmotic fragility of their erythrocytes, whereas the fragility of the red blood cells of D patients is normal. 12 Future advances in research on AD RP will come from the application of new tests such as fundus reflectometry to patients already investigated by the techniques described in this study, longitudinal studies, the investigation of young family members, and histopathological and biochemical studies from donor eyes of properly characterised patients. From such studies it should become clearer whether our attempt at classifying AD RP has a valid basis, whether it needs to be refined and extended, and what are the underlying pathogenetic mechanisms.…”
Section: Disease Mechanismsmentioning
confidence: 99%
“…it has been found that only 8 X-linkcd recessive patients showed decreased T and aspartate [25]. Recently, erythrocyte osmotic fragility has been reported as increased in autosomaldominantly inherited RP in female patients with muliplex RP and in female carriers of the X-linked form of the disease [26].…”
Section: Discussionmentioning
confidence: 99%